A soft X-ray spectroscopic perspective of electron localization and transport in tungsten doped bismuth vanadate single crystals. Issue 46 (15th November 2016) - Jovic, Vedran; Rettie, Alexander J. E.; Singh, Vijay R.; Zhou, Jianshi; Lamoureux, Bethany; Buddie Mullins, C.; Bluhm, Hendrik; Laverock, Jude; Smith, Kevin E.
Abstract : Polarization dependent V L-edge XAS spectra showing anisotropy in the electronic band structure of a W:BiVO4 single crystal. Abstract : Doped BiVO4 is a promising photoelectrochemical water splitting anode, whose activity is hampered by poor charge transport. Here we use a set of X-ray spectroscopic methods to probe the origin and nature of localized electron states in W:BiVO4 . Furthermore, using the polarized nature of the X-rays, we probe variations in the electronic structure along the crystal axes. In this manner, we reveal aspects of the electronic structure related to electron localization and observations consistent with conductivity anisotropy between the ab -plane and c -axis. We verify that tungsten substitutes as W 6+ for V 5+ in BiVO4 . This is shown to result in the presence of inter-band gap states related to electrons at V 4+ sites of e symmetry. The energetic position of the states in the band gap suggest that they are highly localized and may act as recombination centres. Polarization dependent X-ray absorption spectra reveal anisotropy in the electronic structure between the ab -plane and c -axis. Results show the superior hybridization between V 3d and O 2p states, higher V wavefunction overlap and broader conduction bands in the ab -plane than in the c -axis. These insights into the electronic structure are discussed in the context of existing experimental and theoretical reports regarding charge transport in BiVO4 .